Piękna Brama (ὡραία πύλη) w Dziejach Apostolskich.Historyczność i aspekty teologiczne - Rasztawicki, Leszek (Warszawskie Studia Teologiczne, 2019)
The name „Beautiful Gate” appears only twice in the Holy Scripture (Acts 3: 2. 10). There is no evidence in other extra-biblical sources. Neither Jewish historian Josephus Flavius, Mishna and other ancient texts and sources do not mention the gate, which was called “beautiful”. Considering this very rare occurrence of using such name rise many questions. Did such a gate exist? Does Luke use the expression in special narrative and theological purpose? In this article we would like to discuss historicity and archeological proof of the “gate” and find out some narrative and theological aspects.